Cation Exchange Resins as Indicator of In-Season Potassium Supply for Soybean in Kansas - D. A. Charbonnier; M. J. Coelho; D. A. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2020)
The use of ion-exchange resins to measure soil nutrient availability has potential applications for fertilizer recommendations. The objective of this study was to evaluate the relationship between potassium (K) adsorption by cation exchange resins (CER) and K uptake by soybean in field conditions. The study was conducted at two locations in Kansas during 2019. Two treatments were selected to evaluate the CER. Treatments included a check (0 lb K2O/a) and a high K rate with 150 lb K2O/a applied pre-plant and incorporated. The Plant Root Simulator (PRS, Western Ag Innovations, Saskatchewan, Canada) was used as an indicator of in-season K supply to soybean. In addition, whole plant samples were collected at V4, R2, R4, and R6 stages to measure plant K uptake. Soil moisture content was calculated based on soil samples collected at the beginning and end of each burial period. The CER was able to adsorb more K (measured as cumulative adsorption) when K fertilizer (150 lb K2O/a) was applied. Data showed a positive relation between CER values and soil moisture content. Preliminary results from this study suggest that CER can be used as an indicator of K supply, particularly in soils with low soil test K levels.
Keywords: potassium; in-season; soybean